Wifi mobile access with software defined multi-connectivity - Martinez, Victor Manuel Garcia (2019)
The emergence of new applications have made wireless networks evolve towards their fth generation, a novel network paradigm that aims at ful lling a vast range of requirements set by upcoming services and applications. The use of software-de ned networks and virtualization allow creating a service-oriented network, integrated with several radio technologies in its access network. WiFi is one of such technologies and, due to its current ubiquity use, it presents itself as an interesting option due to its popularity, ability to o oad mobile data and good performance in indoor environments. However, WiFi su ers from crucial issues like spectrum interference, connectivity loss, long delay for client association and high latency handover, all of those with direct negative impact on communication reliability. This dissertation propose a SDN architecture to ensure enhanced communication reliability over WiFi wireless networks based on a user access multi-connectivity scheme. This work focuses on splitting the WiFi architecture functionalities in a more e cient way, designed to provide seamless mobility through multi-connectivity, introducing the concept of mobile Access Point in contrast to the traditional operation mode where the client station is the only mobile entity. The proposed architecture is validated through its implementation in real use cases for future 5G verticals, using the concepts of cloud robotics as a critical application to be supported. Results are shown and discussed, demonstrating the feasibility of employing such novel architecture to achieve high reliability service requirements. The results also demonstrate how new softwarization and virtualization technologies can be used in existing wireless architectures to overcome some de ciencies to achieve a successful integration of these wireless technologies in the new 5G network paradigm.